2002
DOI: 10.1007/s004250100650
|View full text |Cite
|
Sign up to set email alerts
|

Phytochelatin synthesis is not responsible for Cd tolerance in the Zn/Cd hyperaccumulator Thlaspi caerulescens (J. & C. Presl)

Abstract: Thlaspi caerulescens (J. & C. Presl, "Prayon") is a heavy-metal hyperaccumulator that accumulates Zn and Cd to high concentrations (40,000 and 4,000 mg kg DW-1 respectively) without phytotoxicity. The mechanism of Cd tolerance has not been characterized but reportedly involves vacuolar sequestration. The role of phytochelatins (PCs) in metal tolerance in T. caerulescens and the related non-accumulator T. arvense was examined. Although PCs were produced by both species in response to Cd, these peptides do not a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

18
97
1
3

Year Published

2003
2003
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 191 publications
(119 citation statements)
references
References 39 publications
(37 reference statements)
18
97
1
3
Order By: Relevance
“…Our direct measurement of the in planta binding environment of Ni in shoot tissue of T. goesingense collected from plants growing in their native habitat revealed that Ni is not bound by PCs in T. goesingense (Figure 4, Table 1), confirming in field collected plant tissue what was observed earlier on laboratory grown plants (Krä mer et al, 2000). PCs have also been shown to play no role in Zn or Cd hyperaccumulation in T. caerulescens Ebbs et al, 2002).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Our direct measurement of the in planta binding environment of Ni in shoot tissue of T. goesingense collected from plants growing in their native habitat revealed that Ni is not bound by PCs in T. goesingense (Figure 4, Table 1), confirming in field collected plant tissue what was observed earlier on laboratory grown plants (Krä mer et al, 2000). PCs have also been shown to play no role in Zn or Cd hyperaccumulation in T. caerulescens Ebbs et al, 2002).…”
Section: Discussionsupporting
confidence: 82%
“…Importantly, this response is only observed after exposure to the metal, and PCs are not produced constitutively (Cobbett and Goldsbrough, 2002). By contrast, naturally metal tolerant plants do not overproduce PC as part of their defense mechanism against Cd, Co, Cu, Ni, or Zn (De Knecht et al, 1992;Schat and Kalff, 1992;Harmens et al, 1993;Salt et al, 1999;Ebbs et al, 2002;Schat et al, 2002). Instead, they display a set of constitutive mechanisms including enhanced efflux and vacuolar compartmentalization (Chardonnens et al, 1999;Van Hoof et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…4 B-D). Recent observations were reported showing that PC levels are generally lower in roots and slightly higher in shoots of the Zn͞Cd hyperaccumulator Thlaspi caerulescens than in the nonaccumulator Thlaspi arvense, despite the higher cadmium concentration in the hyperaccumulator (29). Interestingly, the present study shows that whole-tissue PC levels may not always be a good indicator of the roles of PCs in metal accumulation.…”
Section: Discussioncontrasting
confidence: 77%
“…Strong sulfur (S) ligands like phytochelatins were shown not to be relevant for Cd detoxification in the Cd hyperaccumulator T. caerulescens. Phytochelatin levels are lower in this plant than in the related nonaccumulator T. arvense (Ebbs et al, 2002), inhibition of phytochelatin synthase in hyperaccumulators does not affect their Cd resistance (Schat et al, 2002), and direct measurements of the Cd ligands by EXAFS (Table I) showed that most of the Cd in this species is not bound by strong ligands but by weak oxygen (O) ligands (Kü pper et al, 2004). Thus, the main detoxification strategy in hyperaccumulators is clearly not binding to strong ligands but sequestration of the hyperaccumulated heavy metals.…”
mentioning
confidence: 65%